Corpus Linguistics in English for Specific Purposes (ESP): A Systematic Literature Review - Misnawati Misnawati; Iskandar Iskandar; Saidna Zulfiqar bin Tahir (PT. Global Research Collaboration, 2025)
This study aims to explore the results of empirical research on the corpus linguistics approach in identifying or building vocabulary in English for Specific Purposes (ESP). In ESP, the corpus-based approach has been used in determining specific vocabulary that learners will need within a particular discipline. This study tried to determine how the corpus identifies word lists through a brief overview of the article's reviewed subject. Forty selected articles of 2028 were collected by journals indexed by Scopus, Google Scholars, and Crossref from 1980-April 2022. The results have shown that studies on corpus in ESP are still less attractive among researchers than studies in other fields. There is a lack of publications from year to year, and it even tends to decrease. In addition, many different fields of study have not been the author's concern in building a corpus, such as administration, anthropology, or others. Also, needs analysis and expert validation seem to be ignored, yet they are essential indicators in designing teaching products. So, for further research, it is highly recommended to consider the gaps mentioned to conduct more studies related to corpus compilation in ESP, especially in several fields of science that have never been done before.